The women's auxiliary corps' evaluation of violence against women campaign materials - Alviar, Vaughn Geuseppe G.; Reyes, Jerol Anne C. (2011)
This study focused on evaluating the different Violence Against Women (VAW) campaign materials according to the disposition of the members of the Women's Auxiliary Corps (WAC). This maintains that these women's media preferences are affected by their standpoint as dictated by factors such as lifestyle, age, and demographics. Three women's right organizations in Baguio City were used as sources for the different campaign material used in this study -Stop Abuse and Violence Againts Our Women (SAVE our Women), Department of Social Welfare and Development (DSWD), and Innabuyog- Gabriela. Each of these organizations provided a print material, an audio-visual presentation, and an Internet site. Each of the WAC members was made to rate each of these campaign materials according to the impact made on them. Through this, the researchers were able to identify the most preferred campaign material, the most preferred approach, and the route in which the messages from these campaign materials were processed. The results were also juxtaposed with their standpoint such as educational background, age, educational attainment, sexual preferences and place of origin. This study yielded many valuable results. First, women in extreme societies are basically governed not merely by the demographics such as age or civil status but by two other things that pre-empt their preferences in general: (1) their lifestyles and beliefs as wives or women dreaming to have families someday and (2) the strong culture of loyalty to government fostered in PMA. Moreover, these women's penchant was still determined by the civil rather than military self. This is reflected by the fact that they preferred SAVE Our Women, a private organization. WAC members also preferred AVPs because of its combined substantial and entertaining characteristics. Furthermore, they are generally affected by messages not through the packaging but through the content of the media tools. The results were achieved using Elaboration Likelihood Model (ELM) by Richard Petty and John Cacciopo and Standpoint Theory (SPT) by Julia Wood and Sandra Harding. ELM discusses that people tend to process messages through the central or peripheral route. The central route is basically concerned with the quality of the arguments while the peripheral route is concerned with the packaging. The study ventured into the argument that standpoint affects women's media preferences and the route in which these messages affects their VAW awareness -- Author's abstract.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines Baguio, 2011.
Includes bibliographical references (leaves 150-155)
Keywords: Women's Auxiliary Corps -- Public opinion; Women -- Philipines -- Societies and clubs